Analisis Literasi Sains Mahasiswa PGMI Institut Daarul Qur’an Jakarta - Fitriana Siregar (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Education must be able to, at least, prepare students for three things: a) prepare students for jobs that are not currently available; b) prepare students to have the ability to solve problems whose current problems have not yet arisen, and c) prepare children to be able to use technology whose technology has not yet been discovered. The purpose of this research is to see how the scientific literacy of PGMI students at the Daarul Qur'an Institute is. This research method is a qualitative descriptive analysis, namely by providing a questionnaire of questions related to scientific literacy skills to each student. The sample used was PGMI Daarul Qur'an Institute students in semesters 1, 3, and 5. The results of this study were that some of the students of PGMI Daarul Qur'an Institute already had scientific literacy skills, namely 55% of the students of PGMI Daarul Qur'an Institute Jakarta semester 1, 3, and 5. While the rest do not have scientific literacy skills. This shows that lecturers at the Jakarta Daarul Qur'an Institute, especially those who teach at the PGMI Study Program, must do more learning that emphasizes the scientific literacy skills of their students.